Therapeutic drug monitoring and use of an adjusted body weight strategy for high-dose voriconazole therapy. (20th January 2017) - Richards, Patrick G.; Dang, Kimberlyn M.; Kauffman, Carol A.; Stalker, Kay Lyn; Sudekum, David; Kerr, Lisa; Brinker-Bodley, Michelle; Cheriyan, Beena; West, Nina; Collins, Curtis D.; Polega, Shikha; Malani, Anurag N.
Abstract : Objectives: A high-dose 12 mg/kg/day (6 mg/kg twice daily) voriconazole regimen was recommended by the CDC to treat patients injected with contaminated methylprednisolone acetate that caused a multi-state fungal outbreak in 2012–13. Therapeutic drug monitoring results of this unique regimen are unknown, as is the most appropriate dosing weight for obese patients. We evaluated voriconazole trough measurements for this dosing scheme, as well as the use of adjusted body weight dosing for obese patients. Methods: Voriconazole trough levels were analysed in obese (BMI ≥35 kg/m 2 ) and non-obese (BMI <35 kg/m 2 ) patients who were given initial therapy with 12 mg/kg/day. Results: Of 138 patients, the first steady-state voriconazole troughs were supratherapeutic (>5 mg/L) in 65 (47%) patients, therapeutic (2–5 mg/L) in 57 (41%) patients and subtherapeutic (<2 mg/L) in 16 (12%) patients. Twenty-three patients had pre-steady-state dose decreases due to supratherapeutic levels, with subsequent first steady-state troughs in the therapeutic ( n  =   17) and subtherapeutic ( n  =   6) categories. Voriconazole doses >11 and >8 mg/kg/day produced mainly first steady-state supratherapeutic troughs in 44 obese and 94 non-obese patients, respectively. An initial 12 mg/kg/day was progressively lowered to a median maintenance dose of 8.5 mg/kg/day in the obese and 8.6 mg/kg/day in the non-obese. Conclusions: A high-dose voriconazole regimen produced initial supratherapeutic troughs that required dose adjustment downward by nearly 30%. Adjusted body weight dosing in obese patients resulted in a similar maintenance dose to total body weight dosing in the non-obese, and appears to be a sensible dosing strategy for these patients.